Upaya Guru Kelas dalam Meningkatkan Hasil Belajar Matematika Menggunakan Media Gambar pada Anak Tunagrahita - Siti Hanifah Awalliah, Siti Hanifah Awalliah; Elizabeth Patras, Yuyun; Suchyadi, Yudhie (Jurnal PGSD, 2023)
Efforts of Classroom Teachers in Improving Mathematics Learning Outcomes Using Picture Media in Mentally Disabled Children Thesis for Elementary School Teacher Education Study Program, Teaching and Education Faculty, Pakuan University, Bogor, 2023. The research aims to find out the results of learning mathematics using picture media in children mentally disabled. Taking place at SDN Perwira, Bogor City, it will be held in the even semester of the 2022/2023 Academic Year. This type of research is a case study qualitative research, the research subject is one of the second grade students at SDN Perwira Bogor City who has difficulty in counting. This research data collection technique by observation, interviews and documentation. Data analysis by reducing irrelevant data, presenting data systematically, and drawing conclusions on research findings. The results showed that students who had difficulty in counting.